Exegetical gems from biblical Greek: a refreshing guide to grammar and interpretation - Merkle, Benjamin L. (Baker Academic, 2019)
This accessible supplementary textbook presents 35 illustrative exegetical insights from the Greek New Testament, showing students how the grammatical concepts they are learning affect interpretation.